Assessment of corona loss performance on aging transmission lines using PMU measurements - Pradeep Kumar Gupta; Kaur Tuttelberg; Jako Kilter (Energy Reports, 2023)
This paper presents an assessment of corona loss performance for two overhead transmission lines of different ages using synchronized phasor measurements. In general, it is believed that the aged overhead transmission lines have constrained performance compared to the newer ones as they have been exposed to different environmental conditions for longer period of time. Therefore, in view of availability of synchronized measurements it is possible and of relevance to assess how the corona losses are influenced by line age and what are the main influencing factors. The results of the analysis indicate that there are higher corona losses associated with older overhead transmission lines and respective information is directly applicable for transmission system operators in their system operational planning in order to optimize the purchase of losses from the market.